Gill and Liver Transcript Expression Changes Associated With Gill Damage in Atlantic Salmon (Salmo salar) - Emam, Mohamed; Caballero-Solares, Albert; Xue, Xi; Umasuthan, Navaneethaiyer; Milligan, Barry; Taylor, Richard G.; Balder, Rachel; Rise, Matthew L. (Frontiers in Immunology, 2022)
Gill health represents a significant challenge in the teleost fish aquaculture industry globally, due to the gill’s involvement in several vital functions and direct contact with the surrounding environment. To examine the local and systemic effects accompanying gill damage (which is likely to negatively affect gill function) of Atlantic salmon, we performed a field sampling to collect gill and liver tissue after several environmental insults (e.g., harmful algal blooms). Before sampling, gills were visually inspected, and a gill score was assigned from pristine to severely damaged gills (G0-G3). Using a 44K salmonid microarray platform, we aimed to compare the transcriptomes of pristine and moderately damaged (i.e., G2) gill tissue. Rank Product analysis (5% percentage of false-positives) identified 254 and 34 upregulated and downregulated probes, respectively, in G2 compared with G0. Differentially expressed probes represented genes associated with functions including gill remodeling, wound healing, and stress and immune responses. We performed gill and liver qPCR for all four gill-damage scores using microarray-identified and other damage-associated biomarker genes. Transcripts related to wound healing (e.g., neb and klhl41b) were significantly upregulated in G2 compared with G0 in the gills. Also, transcripts associated with immune and stress-relevant pathways were dysregulated (e.g., downregulation of snaclec1-like and upregulation of igkv3) in G2 compared with G0 gills. The livers of salmon with moderate gill-damage (i.e., G2) showed significant upregulation of transcripts related to wound healing (i.e., chtop), apoptosis (e.g., bnip3l), blood coagulation (e.g., f2 and serpind1b), transcription regulation (i.e., pparg), and stress-responses (e.g., cyp3a27) compared with livers of G0 fish. We performed principal component analysis (PCA) using transcript levels for gill and liver separately. The gill PCA showed that PC1 significantly separated G2 from all other scores. The genes contributing most to this separation were pgam2, des, neb, tnnt2, and myom1. The liver PCA showed that PC1 significantly separated G2 from G0. Levels of hsp70, cyp3a27, pparg, chtop, and serpind1b were the highest contributors to this separation. Gill-damage-responsive biomarker genes and associated qPCR assays arising from this study will be valuable in future research aimed at developing therapeutic diets to improve farmed salmon gill health.